Restoration of Critical-Sized Defects in the Rabbit Mandible Using Autologous Bone Marrow Stromal Cells Hybridized with Nano-β-tricalcium Phosphate/Collagen Scaffolds. (5th November 2013) - Zhang, Xuehui; Xu, Mingming; Liu, Xinggang; Zhang, Feng; Wei, Yan; Meng, Song; Dai, Xiaohan; Duan, Aizhu; Deng, Xuliang
Abstract : Nano- β -tricalcium phosphate/collagen (n- β -TCP/Col) is considered with good osteoconductivity. However, the therapeutic effectiveness of n- β -TCP/Col scaffolds in combination with autologous bone marrow stromal cells (BMSCs) remains to be elucidated for the repair of critical-sized bone defects. In this study, we found that n- β -TCP/Col scaffolds exhibited high biocompatibility in vitro . The introduction of BMSCs expanded in vitro to the scaffolds dramatically enhanced their efficiency to restore critical-sized bone defects, especially during the initial stage after implantation. Collectively, these results suggest that autologous BMSCs in n- β -TCP/Col scaffolds have the potential to be applied in bone tissue engineering.